Advances and applications of nanophotonic biosensors - Altug, Hatice; Oh, Sang-Hyun; Maier, Stefan A; Homola, Jiří (Nature nanotechnology, 2022)
Nanophotonic devices, which control light in subwavelength volumes and enhance light-matter interactions, have opened up exciting prospects for biosensing. Numerous nanophotonic biosensors have emerged to address the limitations of the current bioanalytical methods in terms of sensitivity, throughput, ease-of-use and miniaturization. In this Review, we provide an overview of the recent developments of label-free nanophotonic biosensors using evanescent-field-based sensing with plasmon resonances in metals and Mie resonances in dielectrics. We highlight the prospects of achieving an improved sensor performance and added functionalities by leveraging nanostructures and on-chip and optoelectronic integration, as well as microfluidics, biochemistry and data science toolkits. We also discuss open challenges in nanophotonic biosensing, such as reducing the overall cost and handling of complex biological samples, and provide an outlook for future opportunities to improve these technologies and thereby increase their impact in terms of improving health and safety.
Keywords: nanostruktury; elektromagnetická pole; Spectrum Analysis; Electromagnetic Fields; Nanostructures; analýza nákladů a výnosů; fotony; Cost-Benefit Analysis; biosenzitivní techniky; Biosensing Techniques; Photons; spektrální analýza